A case of pregnancy with multiple fibroids and a second pregnancy POST-Leiomectomy. - lmeida Zambrano, Gustavo A; Chávez Guerrero, Ángelo (Revista Universidad de Guayaquil, 1990)
The case of a primigravida with multiple leiomyomas and a second pregnancy post-leiomyomectomy is described. Observed in the authors’ private practice. She is a 28-year-old patient, who during her pregnancy presented a discrepancy between uterine growth and gestational age, and several uterine tumors were found on palpation, which were confirmed by ultrasound to be uterine fibroids. Her progress during pregnancy was satisfactory. It was decided to perform a cesarean section at 38 weeks of gestation, resulting in a male product, which developed normally. Four tumors of different diameters were removed, which the pathological study reported as fibro leimiomas. The post-operative period was normal, after three and a half months control ultrasounds were performed, reporting a normal uterus. After one year and eight months, she became pregnant again, her gestation progressed normally, it was decided to perform an iterative cesarean section at 39 weeks of gestation, obtaining a male product, in good condition and normal development. The uterus is seen suitable for another pregnancy.